The exon junction complex core factor eIF4A3 is a key regulator of HPV16 gene expression. Issue 4 (30th April 2021) - Meznad, Koceila; Paget-Bailly, Philippe; Jacquin, Elise; Peigney, Anne; Aubin, François; Guittaut, Michaël; Mougin, Christiane; Prétet, Jean-Luc; Baguet, Aurélie
Abstract: High-risk human papillomavirus (hrHPVs), particularly HPV16 and HPV18, are the etiologic factors of ano-genital cancers and some head and neck squamous cell carcinomas (HNSCCs). Viral E6 and E7 oncoproteins, controlled at both transcriptional and post-transcriptional levels, drive hrHPVs-induced carcinogenesis. In the present study, we investigated the implication of the DEAD-box helicase eukaryotic translation initiation factor 4A3 (eIF4A3, ) an Exon Junction Complex factor, in the regulation of HPV16 gene expression. Our data revealed that the depletion of the factor eIF4A3 up-regulated E7 oncoprotein levels. We also showed that the inhibition of the nonsense-mediated RNA decay (NMD) pathway, resulted in the up-regulation of E7 at both RNA and protein levels. We therefore proposed that HPV16 transcripts might present different susceptibilities to NMD and that this pathway could play a key role in the levels of expression of these viral oncoproteins during the development of HPV-related cancers.